2021
DOI: 10.1149/1945-7111/ac275c
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Flexible-Surface Probe for Determining Spatially Heterogeneous Electronic Conductivity of Lithium-Ion Battery Electrode Films

Abstract: Lithium-ion battery electrodes are generally made up of porous, thin films that are structurally heterogeneous on multiple length scales due to the manufacturing process. This in turn causes spatial variability in the electrical properties of the film. This work reports development of a low-cost, flexible probe for measurement of film conductivity and contact resistance to the current collector. When mounted on a moveable stage, the probe can quickly produce maps of electrode electrical properties at sub-milli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…A planned avenue for future exploration is to compare localized ionic transport with localized electronic transport 41 or other properties such as state of charge or state of health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A planned avenue for future exploration is to compare localized ionic transport with localized electronic transport 41 or other properties such as state of charge or state of health.…”
Section: Discussionmentioning
confidence: 99%
“…Average electronic conductivity measurement.-Electronic conductivity of the sample films was determined using a micro-flexible surface probe developed by Vogel et al 41 The technique can be considered an extension of 4-point probe methods and corrects for contact resistance between the probe and the sample film and for the presence of a metallic current collector. Averages were made from measurements at 400 locations to account for spatial variation.…”
Section: Aperture Probe and Experimentsmentioning
confidence: 99%
“…The electrode thickness and the electrolyte bulk conductivity were chosen according to practical experiments. The electrical conductivity of the solid-phase was in the range of values measured using the micro-flexible surface probe developed by Vogel et al 35 With a low ratio of the ionic conductivity to the electronic conductivity of the electrode, the resistance of the solid phase in the transmission-line model becomes negligible, 36 and the impedance depends only on changes in the ionic resistance. Faradaic resistance is set to be large enough to assume that the electrolyte behaves as a "blocking electrolyte," meaning that very little charge-transfer reaction occurs at the solidliquid interface.…”
Section: Virtual Experiments Using Comsol Multiphysicsmentioning
confidence: 97%
“…To address this potential use of the peel test to estimate electrical properties, in this work we quantitatively test the hypothesis that the peel test is an accurate indicator of electrode contact resistance. Our method will be to take measured electrical contact resistance, as estimated by a derivative of the micro-four-point method, 32 namely a micro-flexible-surface probe (μFSP), and explicitly compare with peel test values, namely areal force.…”
mentioning
confidence: 99%
“…In previous work, we have shown that a μFSP can be employed to accurately estimate the contact resistance and bulk electronic conductivity of a thin battery electrode film. 32 Previous iterations of this device have allowed us to accurate estimate electronic properties z E-mail: bmazzeo@byu.edu…”
mentioning
confidence: 99%